How to reduce parental provision of unhealthy foods to 3‐ to 8‐year‐old children in the home environment? A systematic review utilizing the Behaviour Change Wheel framework. (9th August 2018) - Johnson, B. J.; Zarnowiecki, D.; Hendrie, G. A.; Mauch, C. E.; Golley, R. K.
Summary: Background and objective: The effectiveness of obesity prevention interventions to improve children's diet can be enhanced. Deconstructing past interventions can identify components with potential to change behaviour. This systematic review using the Behaviour Change Wheel aimed to examine the behaviour change content of interventions supporting parents of 3‐ to 8‐year olds to reduce provision of unhealthy foods to children. Methods: Ebscohost, Ovid, Scopus and Web of Science were searched. Eligible studies included controlled interventions with active parent involvement, at least one intervention strategy and outcome measure for unhealthy foods ≥3 months from baseline. Seventeen interventions were included describing 18 intervention arms. Results: Interventions frequently targeted parents' reflective motivation ( n = 17) and psychological capability ( n = 15), through education ( n = 15) or enablement ( n = 15) intervention functions and service provision ( n = 18) policy category. Only 24 of the 93 behaviour change techniques were used with an average of five techniques used per intervention. Conclusions: Existing interventions achieving small reductions in unhealthy food intake are homogenous in approach. There is potential to utilize untapped behaviour change techniques, through comprehensive intervention design and behavioural analysis guided by the Behaviour Change Wheel. Interventions targeting opportunity through persuasion, modelling or environmental restructuring, and using different policy categories are urgently needed to provide an evidence base to inform policy and practice.